1999
DOI: 10.1038/13833
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping with biallelic markers in Arabidopsis thaliana

Abstract: Single-nucleotide polymorphisms, as well as small insertions and deletions (here referred to collectively as simple nucleotide polymorphisms, or SNPs), comprise the largest set of sequence variants in most organisms. Positional cloning based on SNPs may accelerate the identification of human disease traits and a range of biologically informative mutations. The recent application of high-density oligonucleotide arrays to allele identification has made it feasible to genotype thousands of biallelic SNPs in a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
133
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(135 citation statements)
references
References 27 publications
1
133
0
1
Order By: Relevance
“…Genome sequencing projects have shown that single base substitutions and/or small insertion-deletion polymorphisms (SNPs) are the most abundant type of DNA variation, e.g., occurring every 100-300 bases in the human genome. SNPs occur frequently in or near coding sequences (Cho et al 1999) and may be the causes of functional differences between alleles. Moreover, the development of EST sequencing projects now makes it possible to discover putative SNPs in silico with subsequent experimental verification.…”
Section: Introductionmentioning
confidence: 99%
“…Genome sequencing projects have shown that single base substitutions and/or small insertion-deletion polymorphisms (SNPs) are the most abundant type of DNA variation, e.g., occurring every 100-300 bases in the human genome. SNPs occur frequently in or near coding sequences (Cho et al 1999) and may be the causes of functional differences between alleles. Moreover, the development of EST sequencing projects now makes it possible to discover putative SNPs in silico with subsequent experimental verification.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of this technique described as tagged microarray marker approach has been demonstrated for humans and pea (Flavell et al, 2003;Ji et al, 2004). However, Affymetrix GeneChips can also be used for SNP genotyping of a number of samples for one or more genes of interest as done in Arabidopsis, where the array AT412 was used for the study of variation in several genes (for example, Eds16 (Cho et al, 1999), Rsf1 (Spiegelman et al, 2000) and FRI (Nordborg et al, 2002)). …”
Section: Snp Genotyping/allelotyping For a Specific Locusmentioning
confidence: 99%
“…On the basis of available sequence data of Arabidopsis accessions, many SNP markers have been detected ; The Arabidopsis Information Resource (TAIR; http:/ /www.arabidopsis.org); Cereon database (http:/ /www.arabidopsis.org/Cereon/index.jsp); and (http:/ /walnut.usc.edu/2010.html). One of the various SNP detection systems (Cho et al 1999) is the recently described SNPWave method (van Eijk et al 2004).…”
mentioning
confidence: 99%